Śivagṛha: religious harmonization and the concept of unity in diversity - Ni Kadek Surpi; I Gusti Putu Gede Widiana; Putu Sri Marselinawati (Institute for Advanced Science Social, and Sustainable Future, 2023)
Prambanan Temple is a Hindu Nusantara Theological Archetype, where the name of the Parabrahman temple becomes Prambanan which means worship of the Supreme God, or the highest temple. The pattern of temple construction that uses the Vāstupuruṣamaṇḍala pattern and the concept of worship is characterized by Hindu Theology which is universal, overshadowing all isms. Relics in the form of Prambanan Temple, the grandest temple in Nusantara, illustrate the glory of Hinduism in the past and the theological concepts and ideas of diversity that are developing today. This qualitative research examines Prambanan Temple as an Archetype of Hindu Nusantara Theology that encourages religious harmonization and upholds the concept of unity amid differences. The research was conducted in several locations, such as the Prambanan Temple Complex, the Indonesian National Museum, the Jakarta National Library, and the Yogyakarta Archaeological Agency. Data analysis was carried out using qualitative analysis known as Ethnographic Content Analysis (ECA), a combination of objective content analysis with participant observation. The original name of Prambanan Temple is Śivagrha which means House of Śiva or Śivalaya-nature of Śiva, as well as the temple of Lord Śiva. Śivagrha is a temple complex worshiping the Tri Murti, namely Brahma, Visnu, and Śiva, as the Creator, Sustainer, and Demolisher. From the structure of the building and the text search, this temple has a Śivaistic concept, namely Śiva is worshiped as the highest Devata. However, it also attracted other devotees and united them with the construction of other deities worshiped in the various temples in this complex. Thus Prambanan became a center of worship, a center for study, a center for Brahmin activities, and a spiritual center or a yatra destination for the wider community.